Analysis of Land Use Evolution of Suzhou Wetlands Based on RS and GIS - Xu, Lirong; Wang, Ruei-Yuan; Zhu, Zhe (International Journal of Environment, Agriculture and Biotechnology, 2023)
The purpose of this study is to analyze the land use evolution and characteristics of Suzhou wetlands. Located in the Taihu Lake basin, Suzhou has abundant wetland resources, covering 339,500 hectares and accounting for 40% of the land area. The huge wetlands have high environmental and ecological indicators. With the support of RS and GIS technology, Landsat OLI 30 m remote sensing images, vector data, 30 m DEM, and other data are used. Through analysis and processing, land use type maps, wetland distribution maps, and research area overview maps are generated, and their land use area, dynamic degree, and transfer matrix are calculated. The results show that from 2013 to 2020, the total area of Suzhou wetlands showed a decreasing trend, with a total change of -8.77%. In the past seven years, Suzhou's urban construction rate has been relatively fast, and the main supply sources of construction land were lakes, mudflats, wetlands, and woodlands. Based on this, the impact of economic development and construction on the protection of environmental ecology should be emphasized and implemented in wetland management and protection strategies in order to promote sustainable environmental development.